STRATEGI DAKWAH MELALUI RADIO (Studi Terhadap Program Hikmah Fajar di Radio Swara Dakwah Al-Amien) - Moh Yunus; Tawvicky Hidayat (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
Da'wah is an iltizam that every Muslim should do. In this case, da'wah should be able to provide solutions to the problems faced by humans, as well as the methods presented in accordance with the situation and conditions of honey. It shows that there is a special strategy to convey da'wah so that the object of da'wah can receive the content of the message of dakwah well. Where radio, is one of the media that is very urgent in delivering the message of da'wah done by dai to his honey. Radio with all its advantages can be reached by various layers of society, both upper and lower, or who are educated or not literate. Related to that, the radio that became the object of this research is Radio Swara Da'wah Al-Amien, especially the program of Wisdom Dawn. Where the program of wisdom dawn is a da'wah program that is carried out in the morning with the concept of lectures with the material conveyed in the form of actual events that occur in society and in accordance with the situation and conditions in society from the perspective of Islam.The problems raised in this research is how the Da'wah Strategy on the program of Hikmah Fajar in Radio Swara Dakwah Al-Amien which is evidenced in two focuses of research are: 1. Researcher Want to know the Strategy of Da'wah on the program of Hikmah Dawn in Radio Swara Dakwah Al-Amien 2. then the researcher Want to know constraints faced during the process of broadcasting the program Hikmah Dawn in Radio Swara Dakwah Al-Amien.To find out more about it, the researcher uses a qualitative field approach. The method of data collection used is the method of interviewing, observation, and documentation. From this method then researchers though and analysis to obtain data or information. The subjects of this study researchers took from the Radio Manager Swara Dakwah Al-Amien, Dai Fajar Morning program, and listeners of the program Hikmah Dawn. For the validity of the data the researcher uses triangulation with two ways: comparing the observation data with the result of interview with triangulation between method that is comparing the state and perspective of someone with various opinions and views of others.From the data obtained, the researchers found that the Da'wah Strategy on the program of Wisdom Dawn in Radio Swara Dakwah Al-Amien covers five principles, namely: philosophical, ability and expertise, sociological, psychological, effectiveness and efficiency. While the obstacles encountered during the process of broadcasting the program Hikmah Dawn in Radio Swara Dakwah Al-Amien namely: Professional Dai and Technical error.